Molecular mutagenesis of ppGpp: turning a RelA activator into an inhibitor - Beljantseva, Jelena; Kudrin, Pavel; Jimmy, Steffi; Ehn, Marcel; Pohl, Radek; Varik, Vallo; Tozawa, Yuzuru; Shingler, Victoria; Tenson, Tanel; Rejman, Dominik; Hauryliuk, Vasili (Scientific reports, 2017)
The alarmone nucleotide (p)ppGpp is a key regulator of bacterial metabolism, growth, stress tolerance and virulence, making (p)ppGpp-mediated signaling a promising target for development of antibacterials. Although ppGpp itself is an activator of the ribosome-associated ppGpp synthetase RelA, several ppGpp mimics have been developed as RelA inhibitors. However promising, the currently available ppGpp mimics are relatively inefficient, with IC50 in the sub-mM range. In an attempt to identify a potent and specific inhibitor of RelA capable of abrogating (p)ppGpp production in live bacterial cells, we have tested a targeted nucleotide library using a biochemical test system comprised of purified Escherichia coli components. While none of the compounds fulfilled this aim, the screen has yielded several potentially useful molecular tools for biochemical and structural work.
Keywords: ligasy; Ligases; Mutagenesis; mutageneze; Escherichia coli; Guanosine Tetraphosphate; guanosintetrafosfát